Effect of Rotten Butter Shock Load on Anaerobic Digestion of Chicken Manure - Gaweł Sołowski; Izabela Konkol; Marwa Shalaby (agriTECH, 2021)
Anaerobic digestion is a popular method for improving fertilizing properties, but there is no report on the effect of shock load with butter on anaerobic digestion of chicken manure. Therefore, this study aimed to investigate the anaerobic digestion of chicken manure with butter addition. The volatile suspended solid (VSS) was set at 20g VSS/L with different butter additions from 0 to 60 g VSS/L and different oxygen flow rate (OFR) from 0 to 2.5 mL/h. The results showed that ammonia ranged from 0.072 g/L to 0.082 g/L, while the volatile acids ranged from 425 mg/L to 325 mg/L. The volatile organic acid was significantly influenced by a change in OFR compared to ammonia, while a correlation between hydrogen and hydrogen sulfide was observed. The results showed that the highest hydrogen and methane production was obtained at butter addition of 30 g VSS/L with OFR 1.4 mL/h with volumes of 78 mL and 25 L respectively. In addition, hydrogen sulfide emissions induced rapid growth with increase in butter concentration.